Perubahan Budaya Kerja Pertanian Lahan Kering Atoni Pah Meto di Kabupaten Timor Tengah Utara - Sasi, Damasius (Paradigma: Jurnal Kajian Budaya, 2016)
The goal of the study is to review changes in dryland farming culture of atoni pah meto in North Center Timor District caused by global climate changes. The research method used was qualitative descriptive: the data collecting method used was interviews, observations, and the document study. Research results prove that the atoni pah meto which consists of eighteen farming rituals, five work patterns, work division between genders, and work ethos, has shifted. It is caused by the interaction of atoni pah meto with other nations, tribes, and ethnic groups, further affected by global climate changes. Climate changes have made a great impact on farmer’s existence and culture. Because of that, the atoni pah meto of NCT District must open up more by accepting changes in the form of program intervention from the governmental and private institutions. It is time to leave shifting cultivation and slash and burn culture, and move to nature friendly farming technologies. Sickle culture will be offered here to replace slash and burn culture, supported by technologies, a more efficient work pattern and work division, and high work ethos, and it is expected that dryland farming of atoni pah meto will persevere.